MULTI-OBJECTIVE OPTIMIZATION MODELING OF INTEGRATED SUPPLY CHAIN FOR SOLID WASTE TREATMENT - Fararah, Emad; Abouel Nasr, Emad; Abbas Mahmoud, Haitham (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Solid waste management (SWM) has been proven as a vital research area, as it contributes in providing a basic and renewal source of production resources like recycled raw materials, fuel and energy sources. Hence, this research investigates the SWM problem by simultaneous consideration of key environmental and economic factors. In this regard, a multi-objective mathematical model is presented for an integrated solid waste supply chain to minimize total costs and environmental impacts while maximizing the recovered energy. The designed supply chain is being modeled as a weighted goal programming (WGP) model to achieve the desired objectives, and this model is solved by applying a simplex-based solution algorithm. In addition, the model and the solution algorithm are validated through the application on real case study data. The comparisons’ results show that the integrated supply chain’s model attains reasonably outperforming results in terms of minimizing the average total cost and environmental impacts.